Preoperative and postoperative blood testosterone levels in patients with acromegaly: a prospective study - Zhang, Duoxing; Guo, Xiaopeng; Feng, Ming; Bao, Xinjie; Deng, Kan; Yao, Yong; Lian, Wei; Xing, Bing; Wang, Hanbi (Frontiers in Endocrinology, 2023)
Purpose: To investigate the prevalence of Low blood Testosterone Level (LTL) and its determinant factors among male active acromegaly patients as well as the effect of surgery on LTL in male acromegaly patients. Methods: A retrospective, single center study focused on 252 male acromegaly patients aged 18 – 60 diagnosed in Peking Union Medical College Hospital from January 2015 to December 2018 were included. Measurements of preoperative and postoperative testosterone, serum Growth Hormone (GH), Insulin-like Growth Factor 1 (IGF-1) and other clinical data were analyzed. Results: 40% of subjects included were diagnosed LTL pre-surgically. Patients were dived into Normal Testosterone Level (NTL) and LTL group based on testosterone level. Significant difference (p  0.01) were found between the presence of macroadenomas, invasion of cavernous sinus, compressions of optic chiasm, serum GH and prolactin levels pre-surgically. Invasion of cavernous sinus (OR = 4.299, p = 0.000) and serum prolactin (OR = 1.023, p = 0.001) were independent predictors of LTL in male patients before surgical intervention. 67.9% LTL patients recovered during follow up with a new-onset rate of 3.4%. BMI, invasion of cavernous sinus, GH, IGF-1, prolactin levels, presence of prolactin secretion tumor and recovery of acromegaly in LTL group were significantly different (p  0.05) compared to NTL during follow up. Presence of prolactin secretion tumor (OR = 0.224, p = 0.001), recovery of acromegaly (OR = 0.168, p = 0.006) were independent predictors of LTL in male acromegaly patients during follow up. Conclusions: Invasiveness of tumor and level of blood prolactin are independent factors for LTL before surgery while GH level and IGF-1 are not. Most of male patients can recover from LTL after tumor restriction surgery, while those recovered of acromegaly has a better chance of recovery from LTL.